2020
DOI: 10.3390/jcm9093027
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Acupoint Indication from Reverse Inference: Data Mining of Randomized Controlled Clinical Trials

Abstract: The specificity of acupoint indication (i.e., reverse inference—diseases for which an acupoint could be used) might differ from the specificity of acupoint selection (i.e., forward inference—acupoints used for a disease). In this study, we explore acupoint specificity through reverse inferences from the dataset of prescribed acupoints for a certain disease in clinical trials. We searched acupuncture treatment regimens in randomized controlled trials included in the Cochrane Database of Systematic Reviews. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Reviewing the classical medical textbooks can provide meaningful information to understand current AP prescriptions [ 23 ]. Despite the fact that classical medical textbooks have affected current AP prescriptions, however, they are not the same [ 25 , 44 ]. Further research based on data obtained from clinicians with different acupuncture styles is necessary to confirm our literature analysis-based results.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the classical medical textbooks can provide meaningful information to understand current AP prescriptions [ 23 ]. Despite the fact that classical medical textbooks have affected current AP prescriptions, however, they are not the same [ 25 , 44 ]. Further research based on data obtained from clinicians with different acupuncture styles is necessary to confirm our literature analysis-based results.…”
Section: Discussionmentioning
confidence: 99%
“…The Acusynth database comprised acupoint combinations for 30 disorders from 30 CDSRs. 12 , 16 , 17 , 18 Studies have described the major acupoint selection patterns in both ancient and modern practice. 3 , 17 …”
Section: Methodsmentioning
confidence: 99%
“… 12 , 16 , 17 , 18 Studies have described the major acupoint selection patterns in both ancient and modern practice. 3 , 17 …”
Section: Methodsmentioning
confidence: 99%
“… 4 , 9 Additional acupoints indications have also been revealed based on the relationships between individual acupoints and diseases found in clinical trials listed in the Cochrane Database of Systematic Reviews (CDSR). 10 A subsequent analysis of the same database found that commonly used acupoints, most of which were five-phase acupoints, have been used to treat various pain conditions. 11 , 12 Hierarchical cluster analysis demonstrated that the spatial pattern of each meridian's indication was similar to the route of the corresponding meridian.…”
Section: Introductionmentioning
confidence: 99%